Clinical Validation of Mobile Cardiotocograph Device for Intrapartum and Antepartum Monitoring Compared to Standard Cardiotocograph: An Inter-Rater Agreement Study - Manoja Kumar Das; Reva Tripathi; Neeraj Kumar Kashyap; Sunita Fotedar; Surender Singh Bisht; Asmita M rathore; Aakanksha Raghav (Tehran University of Medical Sciences, 2019)
Objective: Electronic fetal monitoring (EFM) using cardiotocograph (CTG) is commonly used both to assess fetal wellbeing in late antepartum and for intervention during intrapartum period. We validated the performance of indigenously developed mobile cardiotocograph (CTG) device with wireless probes compared to standard CTG device. Materials and methods: We sequentially used mobile and standard CTG devices in 495 pregnant women in labour and 359 pregnant women with gestation > 32 weeks. The CTG interpreted by two independent obstetricians in a blinded manner were compared to estimate the agreement by kappa (k) statistic. Results: High level of agreements between mobile and standard CTG devices for both intrapartum (87.9%; kappa 0.61) and antepartum monitoring (91.2%; kappa 0.60) were observed. Most of the pregnant women (80% in intrapartum and 70% in antepartum groups) and all nurses and obstetricians preferred the mobile CTG device over standard CTG device. Conclusion: The mobile CTG device can reliably be used for both intrapartum and antepartum monitoring instead of the standard CTG devices. The smaller size, portability and ability to transmit the recordings for second opinion make it suitable for use by midwives for appropriate triaging and referral. Wider availability of CTG and interpretation support at the peripheral facilities would assist identifying at-risk pregnancies and foetuses for timely referral and appropriate action to reduce perinatal deaths, stillbirths and birth asphyxi.